FEATURES OF THE INVESTMENT CLIMATE IN UKRAIN - Чіп, Л. О. (Scientific Progress & Innovations, 2014)
The features of the main problems of the investment climate in Ukraine, its crucial importance to the promotion of the dynamics of socio-economic development and possibility of updating on this basis of the national economy have been analyzed. The main features and trends of investment processes in Ukraine and ways of improving the state policy in the field of investment, as well as measures to improve the legal framework in the field of investment activities have been examined. The attention has been focused on the fact that Ukraine is dominated by negative assessments of the investment climate, because domestic investment is not enough to provide high long-term trend, and the rate of foreign direct investment - investment as a stimulant - slowed considerably. Necessity, that at the present stage of development of the economy, foreign direct investment is an integral part of its normal operation. The fundamental importance of investment for a clear definition of national interests, taking into account the effects of the geopolitical environment has been highlighted.